A natural refuge for an Anobiidae species (Tricorynus sp) in persistent pods of Acacia caven (Mol.) in Uruguay - Rojas Rouáe, D.=700 1 Grille, G.; Baáo, C.
(Es, En)
Ilus., 12 ref.
Keywords: ACACIA CAVEN; SEMILLAS; DAÑOS; INSECTA; ESPAÑA; ANABIIDAE; BOLETIN DE SANIDAD VEGETAL: PLAGAS